Implementation of Sustainable Procurement in Purchasing at Hotel X - Dewi, Ni Putu Eka Amaylia Kusuma; Sumariati, I Dewa Ayu Rai; Lilasari, Luh Nyoman Tri (Transpublika Publisher, 2025)
Consumer demand for environmentally friendly practices is pushing hotels to change. Hotel X has implemented an ESG Policy, prioritizing sustainable procurement. This means focusing on local and environmentally certified suppliers instead of just cost and quality. However, transitioning to this model presents challenges. Therefore, this study aims to examine the implementation of sustainable procurement within the purchasing department at Hotel X. This study utilizes a qualitative descriptive method by engaging two selected informants. The data analysis technique consisted of several stages: data collection, data reduction, data presentation, and conclusion drawing. The data were obtained through a combination of interviews, observations, and document analysis. The results indicate that four out of six principles of the Environmental Social Governance (ESG) Policy in the area of materials sourcing and efficiency have been successfully implemented. The remaining two principles have not been fully implemented due to several challenges. These challenges include phased implementation, limited availability of certified local suppliers, low supplier awareness, and difficulties in sourcing renewable raw materials that meet the hotel’s operational needs. These findings provide significant contributions to the development of sustainable procurement practices in the hospitality sector and open up opportunities for broader application across other industries. Organizations can formulate more targeted and effective strategies to facilitate the implementation of sustainable procurement, which in turn contributes to improving the hotel's reputation, increasing customer satisfaction, and promoting environmental sustainability.